The impact of online learning for the growth and development of Junior High School Students in Medan - Akhyar, Akhyar Anshori; Yusuf, M. Yusuf Imfazu; Dinda, Dinda Ayu Lestari (COMMICAST, 2022)
The Covid-19 pandemic has greatly impacted all lines of people’s lives, including the teaching and learning process. In order to anticipate the spread of Covid-19, the government enforces an online teaching and learning process. Activities that take place online, of course affect the level of student acceptance and also the physical and psychological conditions of students.  This study aims to determine the impact of online learning on the growth and development of junior high school students in Medan City. The research was conducted through a quantitative approach with the type of correlational research. The results of the study found that online learning, affect students’ psychology as expressed by about 54,75% respondents. In addition, the absence of parental support and motivation in accompanying students during online learning as stated by about 62,25% of respondents certainly makes students feel less cared for.